Matrices poliuretánicas biorreabsorbibles para aplicaciones en ingeniería de tejidos - Caracciolo, Pablo C. (2010)
Segmented polyurethanes (SPU) are block copolymers widely used as biomaterials due to their good biocompatibility and chemical and structural versatility, characteristics that allow a broad range of properties. In the biomedical field, SPU elastomers are mainly used in biostable implants and several biomedical devices. However, polyurethanes are susceptible to hydrolytic and oxidative degradation in physiological conditions, allowing the development of temporal applications for regenerative medicine. In this thesis, the design, synthesis, characterization, properties and processing of a series of novel bioresorbable polyurethane systems is presented. These materials are of interest for applications in tissue engineering. The polyols and chain extenders used in the synthesis of SPU were designed to promote microphase separation and semicrystalline soft-domain formation. Moreover, the use of those components and aliphatic diisocyanates ensure the bioresobability of their non toxic degradation byproducts. The effect of chain extender and hard segment structure and chemical composition in the thermal and mechanical properties of SPU films was analyzed. The different chemical structure and symmetry of both chain extenders and hard segments affected the phase separation. Thermodynamically, the synthesized HDI-based hard segments exhibited lower phase mixing with PCL soft segments than other HDI-based hard segments reported in the literature. The materials were soft elastomers, as demonstrated by the mechanical properties in tensile, loading cycles and tear. The in vitro biological properties, as determined by using several analytical techniques, displayed low platelet adhesion and activation, low thrombus formation, and low cytotoxicity, showing a priori a good biocompatibility of these materials. The electrospinning technology allowed the preparation of micro/nanofibrous polyurethane scaffolds by an appropriate selection of the processing parameters and solution properties. Thermal and mechanical properties of these micro/nanofibrous scaffolds were analyzed and compared with the obtained for the films. The characteristics of the processing technique led to different crystalline morphologies. The scaffolds displayed a highly interconnected porous structure, microstructure useful for soft tissue engineering and drug delivery applications. The degradative behavior of films and scaffolds were studied in physiological and accelerated conditions. The evaluation of hydrolytic and oxidative stability as a function of composition, structure and morphology of each system was performed. Finally, polyurethane networks with controlled hydrophilicity were obtained by using hydrophilic and hydrophobic monomers. Thermal and water uptake were studied as a function of the composition for each formulation. The presence of chemical and physical crosslinking introduced an interesting feature that affected the observed properties.